Analisa Jaringan Internet dengan Quality of Service Pada Teknologi Wireless Local Area Network - Moh Tri Adi Prasetyo; Wiwin Sulistyo (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
At present the development of technology is very rapid and has succeeded in creating new technologies, especially in the field of internet technology. The presence of internet technology has a good impact on human life. Therefore, with the existence of internet technology, everyone can connect between regions in one internet network which is quite large and there are no other regional boundaries. The internet is a combination of computers that are connected to each other with the help of cables or fiber optics, telephone lines, and satellites. PT Solo Jala Buana is an internet service provider that can be used in Indonesia, offering various internet packages with speeds ranging from 1 Mbps to 100 Mbps which can be used both wirelessly and via LAN. Service standard or Quality of Service (QoS) is the ability of a network to provide data traffic services with delay, throughput, and packet loss parameters. QoS can be used to check This research found QoS measurement results on 50 Mbps services which were analyzed by live stream, which resulted in the conclusion that the service is quite stable when used when users are busy or quiet, but improvement is still needed to achieve the desired results